Novel Transgenic Mouse Model for Studying Human Serum Albumin as A Biomarker of Carcinogenic Exposure - Sheng, Jonathan (Chem Res Toxicol, 2016)
Albumin is a commonly used serum protein for studying human exposure to xenobiotic compounds, including therapeutics and environmental pollutants. Often, the reactivity of albumin with xenobiotic compounds is studied ex vivo with human albumin or plasma/serum samples. Some studies have characterized the reactivity of albumin with chemicals in rodent models; however, differences between the orthologous peptide sequences of human and rodent albumins can result in formation of different types of chemical-protein adducts with different interaction sites or peptide sequences. Our goal is to generate a human albumin transgenic mouse model that can be used to establish human protein biomarkers of exposure to hazardous xenobiotics for human risk assessment via animal studies. We now have developed a human albumin transgenic mouse model and characterized the genotype and phenotype of transgenic mice. The presence of human albumin gene in the model mouse genome was confirmed by genomic PCR analysis, while the liver-specific expression of the transgenic human albumin mRNA was validated by RT-PCR analysis. Further immunoblot and mass-spectrometry analyses indicate that the transgenic human albumin protein is a full-length, mature protein, which is less abundant than the endogenous mouse albumin that coexists in the transgenic mouse serum. The transgenic protein was able to form ex vivo adducts with a genotoxic metabolite of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine, a procarcinogenic heterocyclic aromatic amine formed in cooked meat. This novel human albumin transgenic mouse model will facilitate the development and validation of albumin-carcinogen adducts as biomarkers of xenobiotic exposure and/or toxicity in humans.